Importance of ISO 9002 towards small manufacturing firm, case study analysis: Kelemak, Alor Gajah Industrial Area / Md Faizul Md Fadzil - Md Fadzil, Md Faizul (Faculty of Business Management, 2001)
The purpose of this study is to study the importance of ISO 9002 to Small Manufacturing Firm (SMF), case study analysis: Kelemak, Alor Gajah Industrial Area. The objective of this study are: (1) To identified the level of knowledge of SMF towards quality as well as ISO 9002, (2) to evaluate programs and effort carried out or done by the government, (3) to investigate the impact of implementing the ISO 9002 in SMF in three aspects, profit will increased, cost will reduced and efficiency will be ensured. A total of 30 respondents were involved in the study. Therefore, the analysis of survey results is based on 30 positive responses. Data were coded and analyzed using the SPSS version 10.0. Particularly chapter 5 of this report is to care outline of survey with regards of the finding and analysis of this study. In general ISO 9000 series especially ISO 9002 standards give benefits to company such as greater customer loyalty, improvements in market share, greater productivity and cost reduction. Employee and employer should give full commitment for their company in order to improve quality of the product and services that company offered. Employees have to expose about ISO 9000 standards and importance of it. Several limitations were faced in completing this study. The sampling size was small compared to actual number of population in the Kelemak, Alor Gajah Industrial Area. Therefore, to obtain the correct sample size would requite a longer time frame and effort. Generally, the conclusion of the outcome decided from survey analysis, finding and recommendations given. In this regard, it is hope that this research will provide useful information as a basic to improve quality towards achieving ISO 9002 standards at Kelemak, Alor Gajah Industrial Area